APPLICATION OF MULTI-ARRAY ELECTRICAL RESISTIVITY TOMOGRAPHY IN PT. BUKIT BAIDURI ENERGI COAL MINING-EAST KALIMANTAN - Piter Lepong; Supriyanto Supriyanto; Sri Wahyuningsih; Hardiyanto Hardiyanto (Puslitbang tekMIRA, 2018)
Multi-array Electrical Resistivity Tomography survey was conducted in coal mining concession of PT. Bukit Baiduri Energi at the Marandai pit, Loa Janan District, Kutai Kartanegara-East Kalimantan. Data acquisition has been done using the MAE-X612 unit with 48 electrodes and 5 meters interval and the maximum length of the survey was 235 meters. The aim of the survey is to analyze resistivity images from three different electrodes configurations for interpreting coal seams and other lithologies. We deployed three configurations, including Wenner-Schlumberger, Dipole-Dipole, and Pole-Dipole in one traverse. The resistivity images analyses were constrained using geological and geophysical logging. The result shows that the Wenner-Schlumberger array is the reliable result comparing to the dipole-dipole and pole-dipole arrays. This technique will apply for further assessment to provide the reliable result in this coal mining concession. Electrical Resistivity Tomography offers rapid mapping for shallow mine working up to 45-meter depth. This method can be applied to one or two hour’s measurements with 48 electrodes with maximum 5-meter electrodes interval. This method offers the possible saving of drilling cost by using resistivity profile for coal seam correlation instead of conducting more drilling.